Excess returns and the distinguished player paradox - Matthias Blonski; Ulf von Lilienfeld-Toal (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2008)
Suppose the value of a firm is endogenously determined by a manager's costly effort. We call this manager a distinguished player if he also can trade shares of the firm on a market. Arbitrage-free asset pricing theory suggests that the equilibrium market price reflects the value increasing contribution of a distinguished player. Trade at this price, however, cannot be an equilibrium of a market game since due to private effort costs, shares have a lower value to the distinguished player as compared to other investors. Why? The distinguished player himself can gain by selling at this price and in turn reduce effort. By merging asset pricing and corporate finance concepts we solve this distinguished player paradox and show how this asymmetry in valuations can systematically bring about a trade price strictly below the equilibrium value of the company. This implies that buyers enjoy excess returns on their investment and is thereby at odds with the efficient markets hypothesis. It further involves a substantial reinterpretation of traditional no-arbitrage towards a game-theoretic understanding. The empirical prediction that companies with a distinguished player yield excess-returns was confirmed for the sample of S&P500 firms and S&P1500 firms in a companion paper by von Lilienfeld-Toal and Runzi (2007). Our results are shown to be robust with respect to trading rules, discrete versus continuous effort, trading costs, noise traders, and price taking behavior.
Keywords: G12; G32; C72; D43; D46; 330; excess returns; underpricing; no-arbitrage; asset pricing; corporate finance